Gliding associated proteins play essential roles during the formation of the inner membrane complex of toxoplasma gondii - Harding, Clare R.; Egarter, Saskia; Gow, Matthew; Jiménez-Ruiz, Elena; Ferguson, David J. P.; Meissner, Markus (PLoS pathogens, 2016)
The inner membrane complex (IMC) of apicomplexan parasites is a specialised structure localised beneath the parasite’s plasma membrane, and is important for parasite stability and intracellular replication. Furthermore, it serves as an anchor for the myosin A motor complex, termed the glideosome. While the role of this protein complex in parasite motility and host cell invasion has been well described, additional roles during the asexual life cycle are unknown. Here, we demonstrate that core elements of the glideosome, the gliding associated proteins GAP40 and GAP50 as well as members of the GAPM family, have critical roles in the biogenesis of the IMC during intracellular replication. Deletion or disruption of these genes resulted in the rapid collapse of developing parasites after initiation of the cell cycle and led to redistribution of other glideosome components.
Gesehen am 30.04.2020